Authorized or Off-Label Use? A Structured Analysis of Summaries of Product Characteristics with Regard to Authorization in Pediatrics - Herzig, Markus; Eisenhofer, Simone; Ruschkowski, Meike; Neubert, Antje; Bertsche, Astrid; Bertsche, Thilo; Neininger, Martina Patrizia (Pharmaceutical Medicine, 2024)
Purpose: The Summary of Product Characteristics (SmPC) is required to provide unambiguous information on the authorized use of a medicinal product. Therefore, we performed a structured analysis of the information provided for pediatric patients in current SmPCs. Methods: In the German SmPC of the medicinal products of 452 active substances, we analyzed for each of the listed indications whether information on pediatric use was available in Sects. 4.1–4.4 of the SmPC and, if so, whether it was unambiguous. Information was considered unambiguous if it indicated an exact age- or weight-related specification. The analysis also considered the type of marketing authorization and the date of marketing authorization, either before or after the Pediatric Regulation 2007 came into force. Results: Among the 30,354 identified indications in 8464 SmPCs, unambiguous information was found for 72.4% (21,974/30,354) of the indications. Of these, 45.4% (9967/21,974) disclosed a contraindication for the entire population under 18 years of age. The proportion of unambiguous information was higher for medicinal products with centralized marketing authorization (86.5% [1449/1676]) than for those with a national one (71.6% [20,525/28,678]; p < 0.001). A higher proportion of unambiguous information was found for the marketing authorization period 2007–2021 compared with 1996–2006 (1996–2006: 63.8% [7466/11,694]; 2007–2021: 82.1% [12,349/15,040]; p < 0.001). Conclusion: For about a quarter of all indications, no or only ambiguous information was available for pediatric patients. The measures initiated in recent years to increase pediatric-specific information in SmPCs should be intensified in order to improve drug safety in children and adolescents.
CRIS-Team Scopus Importer:2024-04-05